IDENTIFIKASI KESALAHAN SISWA MENGGUNAKAN NEWMAN’S ERROR ANALYSIS (NEA) PADA PEMECAHAN MASALAH OPERASI HITUNG BENTUK ALJABAR - Desy Yusnia; Harina Fitriyani (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Problem solving is the important part of mathematic curriculum. Although, there are many mistakes from the students in mathematic problem solving,especially on counting operation of algebra form. Newman’s error analysis(NEA) is a method that is used to analyze the students error with five stages,there are reading, comprehension, transformation, process skills, and writingthe final answer (encoding). This research aim to know the kind of error thatwas done by the students in solving the counting problem on algebra based onNEA and the influence factors of the error that cause by students. This research is a descriptive qualitative research. The subject is students grade VII-F SMP N 1 Wonosari. The data collecting technique is problem solving test and interview. The data analysis according to Miles and Huberman, which is data reduction, data presentation, and making conclusion. The results of this research showing that the kind of error from the subject research on solving the counting problem of algebra form is error on comprehension the problems, error on transformation question, error on process skill, and error on writing the final answer. The most common error is on process skill stage. It cause the factor because the students are not carefully, can not write the right formula, and false in counting. Keywords: Newman’s Error Analysis (NEA), Problem solving.